Treatment of face and scalp solar (actinic) keratosis with daylight‐mediated photodynamic therapy is possible throughout the year in Australia: Evidence from a clinical and meteorological study. (31st March 2015) - Spelman, Lynda; Rubel, Diana; Murrell, Dedee F; See, Jo‐Ann; Hewitt, Daniel; Foley, Peter; Salmon, Robert; Kerob, Delphine; Pascual, Thierry; Shumack, Stephen; Fernandez‐Penas, Pablo
Abstract: Background/Objectives: Solar (actinic) keratosis (AK) is an emergent concern worldwide and is associated with an increased risk of development of non‐melanoma skin cancer, especially squamous cell carcinoma. Daylight‐mediated photodynamic therapy (DL‐PDT) using methyl aminolaevulinate cream has proved to be an effective, nearly painless, and more convenient alternative to conventional PDT for the treatment of AK. In a phase III, randomised, controlled trial performed in Australia, the mean irradiance (light intensity) received by patients during DL‐PDT treatment, assessed via a spectroradiometer, was 305 W/m 2 (min. 40 to max. 585 W/m 2 ) with similar efficacy irrespective of intensity or dose. The objective of the present meteorological study was to assess the suitability of natural daylight to perform DL‐PDT for the treatment of face and scalp AK during different periods of the year and different geographical locations and latitudes across Australia. Methods: To determine daylight irradiance during a complete year in eight different geographical locations throughout Australia, we used meteorological software (Meteonorm, Meteotest, Bern, Switzerland), and available solar radiation and weather data from 1986–2005. Results: The average daily irradiance remained within the levels (40–585 W/m 2 ) measured during the clinical DL‐PDT study in Australia, throughout the year and in all geographical locations investigated (yearly average from Darwin 548 W/m 2 to Hobart 366 W/m 2 ). Conclusions: DL‐PDT for the treatment of face and scalp AK in Australia can be performed effectively throughout the entire year as long as weather conditions permit daylight exposure and allow participants to remain under direct light for 2 h.